THE EFFECT OF WORKPLACE SPIRITUALITY ON UNIVERSITY MEMBERS’ AFFECTIVE COMMITMENT, CONTINUANCE COMMITMENT AND NORMATIVE COMMITMENT - Chelliah, Thamil Durai,; Chan, Ling-Meng,; Lau Say Min, Claudia; Jaganathan, Mathivannan; Koay, Ying-Yin, (International Journal of Psychosocial Rehabilitation, 2020)
Objective: This study intended to study the influences of workplace spirituality on organizational commitment among Malaysia University members. Research Methodology: 240 respondents from 5 different regions were participated in this study. Selfadministrated questionnaire survey was used to collect the data from the respondents. The data was analyzed via partial least square structural equation modelling. Finding: Workplace spirituality was found significantly influence the university members’ organizational commitment, specifically on the three dimensions namely affective, continuance and normative commitment. Research Implication: The presence of workplace spirituality can improve and enhance the trust climate of the organization, which effectively develop positive organizational commitment among members. Originality / Value: Through this study, it ascertained that workplace spirituality is playing essential influences in enhancing organizational commitment of university members. In order to improve the organizational commitment of members, the university should find ways to implant this intangible motivation variable to them.